Circulating antibodies in human echinococcosis before and after surgical treatment - Todorov, T. (1979)
Antibody levels in 89 patients who had been operated on for hydatid disease were studied over a period of 4 years by complement fixation, latex agglutination, bentonite flocculation, and passive haemagglutination tests. The geometric mean titres were much higher in patients with liver echinococcosis than in those whose lungs were affected. In the first month after operation, an increase in antibody level was observed more often in the former than in the latter. The raised level usually persisted for 3-6 months. In one group of 77 patients, the serological tests either became negative 6 months to 2 years after operation or remained positive during the entire postoperative period. In the other 12 patients, who had recurrent echinococcosis, the tests did not become negative, although there was a reduction in antibody levels during the first and second postoperative years in 6 patients, followed by a rise when the disease recurred. Antibody levels remained high during the entire observation period in the other 6 patients. The prognosis can be considered favourable in patients with low pre-operative titres, or negative tests, provided the tests remain negative up to the end of the first year after operation or become negative within one and a half years. Where there is only a small reduction in antibody titre, the prognosis may still be favourable if the decrease continues to fall up to the end of the second year. Since a drop in antibody titres occurred in certain cases with recurrent infection, it is advisable to defer an opinion on the prognosis until the end of the second year. If the fall in antibody titres is followed by a steady rise, or if they remain high or show slight fluctuations, a recurrence is almost certain.